2018
DOI: 10.1177/2378023118809264
|View full text |Cite
|
Sign up to set email alerts
|

Text Analysis with JSTOR Archives

Abstract: I provide a visual representation of keyword trends and authorship for two flagship sociology journals using data from JSTOR’s Data for Research repository. While text data have accompanied the digital spread of information, it remains inaccessible to researchers unfamiliar with the required preprocessing. The visualization and accompanying code encourage widespread use of this source of data in the social sciences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Although the present study relied heavily on Holifield's (2005) historical study of pastoral care, future research in this vein might focus on Laderman's (1999, 2005) historical study of death in America, Collins’ (1998) study of philosophical evolution, or Szacki's (1979) history of sociological thought. The availability of large‐scale digital text repositories only makes this type of research more feasible (Bernau 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Although the present study relied heavily on Holifield's (2005) historical study of pastoral care, future research in this vein might focus on Laderman's (1999, 2005) historical study of death in America, Collins’ (1998) study of philosophical evolution, or Szacki's (1979) history of sociological thought. The availability of large‐scale digital text repositories only makes this type of research more feasible (Bernau 2018).…”
Section: Discussionmentioning
confidence: 99%
“…A study by Anson and Moskovitz 11 in 2021 showed the word patterns in the research output of applied science faculties. Bernau 12 , through his study in 2018, provided keyword trends and authorship to flagship sociology journals using data from JSTOR. The research conducted by Fallucchi and others 13 in 2022 shows how digital humanities tools help users to identify structural and linguistics patterns and research.…”
Section: Review Of Related Literaturementioning
confidence: 99%